PARTISIPASI MASYARAKAT DALAM MELESTARIKAN KAWASAN HUTAN LINDUNG GUNUNG BUDUK SEBAGAI SUMBER AIR BERSIH DI DESA IDAS KECAMATAN NOYAN KABUPATEN SANGGAU - Damiati, Veronika; Lumangkun, Augustine; Dirhamsyah, M (JURNAL HUTAN LESTARI, 2015)
Forest communities have a very significant role for the life of the community or communities that are around the area of protected forest. is the source of life that is very important for humans, animals, plants and microorganism of small though. Sometimes many people do not realize that they live around the area that are a boon for survival that can continue living as they should, so that public participation in addressing any action that many pollute, negate and endanger water sources and protected forest areas in needed. The methods used in this research study is descriptive in the form of a structured interview survey technique using research tools such as questionnaires. The number of respondents in this research study were as many as 75 respondents. From the result of the study determined that public participation in conserving the area of protected forest as a source of clean water are likely to. Keywords : Participation, community, protected forest, source of water, forest in Idas village